1985
DOI: 10.1111/j.1559-1816.1985.tb02269.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Injustice on the Endorsement of Political Leaders1

Abstract: Recent public opinion polls have suggested that there is a striking lack of public support for national political leaders and institutions. The two studies discussed in this paper explore why public evaluations of political leaders and institutions are low. In particular, they examine the role of perceived injustice in creating dislike for and distrust of leaders and institutions. This focus upon justice is contrasted with the more traditional focus upon the level of outcomes received from the political system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(127 citation statements)
references
References 34 publications
4
119
0
4
Order By: Relevance
“…Folger and Konovsky (1989) also showed similar findings that pay rise and job satisfaction significantly related to the perception of distributive justice. Tyler et al (1985) reported that both procedural and distributive justice contribute significantly to variance in outcome satisfaction. Even though both of justice contribute to variance in satisfaction, but contribution of distributive justice is nearly twice that of procedural justice.…”
Section: The Effect Of Distributive On Job Satisfactionmentioning
confidence: 99%
“…Folger and Konovsky (1989) also showed similar findings that pay rise and job satisfaction significantly related to the perception of distributive justice. Tyler et al (1985) reported that both procedural and distributive justice contribute significantly to variance in outcome satisfaction. Even though both of justice contribute to variance in satisfaction, but contribution of distributive justice is nearly twice that of procedural justice.…”
Section: The Effect Of Distributive On Job Satisfactionmentioning
confidence: 99%
“…While the basic finding about the importance of decision control has been reiterated over the years (see Lind and Tyler 1988), subsequent research has also illustrated that control over the process can rank as more important than control over decisions, and that process control can be important even in the absence of decision control (Lind, Lissak, and Conlon 1983;Tyler, Rasinski, and Spodick 1985;Tyler 1987Tyler , 1990). Thus, not only is voice important as an instrumental means of influencing decisions, but voice can have value in its own right.…”
Section: Voice Influence and Satisfactionmentioning
confidence: 99%
“…This is different from the concept of outcome fairness, which relates to the distribution of the costs and benefits within society [15]. Much evidence suggesting that people are more likely to accept policy decisions that come from fair procedures than those from unfair procedures has accumulated within the field of social psychology [14,16,17]. For example, Tyler et al [17] found that the endorsement of the Reagan administration's tax policies in the United States was more strongly influenced by judgments of procedural fairness than by other outcome-related concerns.…”
Section: Protected Values and Procedural Fairnessmentioning
confidence: 99%